The impact of precautionary lockdown measures during COVID-19 on eating behaviour and lifestyle - Aldhwayan, Madhawi; Alabdulkader, Balsam (Progress in Nutrition, 2022)
Background: Eating behaviour and lifestyle are highly susceptible to changes in the individual’s external environment. COVID-19 pandemic resulted in policies that severely impacted individual habits and daily routines. Growing literature highlights the adverse psychological impact of COVID-19 on eating behaviour and lifestyle. Methods: This study aimed to assess eating behaviour and lifestyle in Saudi Arabia during the strict lockdown. A self-reported online questionnaire was used to assess eating behaviour and lifestyle changes, including physical activity, sleep, and digital device use compared to that pre-lockdown. Results: A total of 1,860 participants completed the questionnaire. Weight gain was reported by 31%, whereas 41% reported decreased physical activity. The use of digital devices increased by 70%, with 59% of participants reporting symptoms of digital eyestrain. Mostly, 72% reported decreased fast-food delivery, mainly due to fear of contracting the virus. This decrease paralleled a 66% increase in home cooking. On the contrary, 15% reported weight loss, and 21% increased their physical activity. Conclusion: These findings provide important insight into the effects of COVID-19-related lockdown on eating behaviour and lifestyle.